The Effect of Dividends as a Moderating Variable on Firm Value LQ45 on the Indonesia Stock Exchange - Bakhtiar, Fauzia; R, Rusdi (Pascasarjana STIE Amkop Makassar, 2025)
The policy regarding the percentage of retained earnings and dividends to be distributed is one of the important strategic decisions that must be chosen by the Company's management in order to attract investor interest and influence investor perceptions of the Company's prospects . This study aims to determine the effect of dividends as a moderating variable on the influence of retained earnings on the firm value of LQ45 on the Indonesia Stock Exchange. The type of research is associative quantitative. Location and Time of the study The research was conducted on LQ45 index companies listed on the Indonesia Stock Exchange website www.idx.go.id in 2025 and the observation year of the LQ45 index was 2015-2024. The type of research data is secondary data in the form of annual financial reports of Manufacturing Companies listed on LQ45 2015-2024. The research variables are: Retained earnings (X), Dividend (Z), and firm value (Y). Based on the research results, the direct relationship between Retained earnings and firm value shows a positive and significant influence. Meanwhile, the interaction between Retained earnings and Dividend on firm value has a positive influence but is not statistically significant. The direct influence of Dividend on firm value shows no significance. Keywords: Dividend , retained earnings, firm value